Recognition of foreign professional qualifications - the Federal Government's new Recognition Act - Fohrbeck, Dorothea [Verfasser] (My University, 2013)
"Many members of the working population in Germany possess professional qualifications which they have gained abroad and which are urgently needed on the German labour market. In the past, these people could often not be optimally employed due to the absence of standards and procedures to assess their qualifications. The Assessment and Recognition of Foreign Professional Qualifications Act ('Recognition Act'), which entered into force on 1 April 2012, introduces a standardized national procedure and criteria for the assessment of foreign professional qualifications - at least for professions that are regulated by Federal law. It improves the opportunities for people who gained their qualifications abroad to work in their trained profession. The Act also makes Germany a more attractive workplace for international skilled staff. This article provides background information on the history of the legislation, introduces some of the most important contents and finally identifies further action required to implement the Act." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Anerkennungsgesetz; Auslandsqualifikation; Anerkennung; Verfahren